A Study of Teacher Stereotypes: How Do Tuition-Free Teacher Candidates and General Undergraduates Think about Middle School and University Teachers in China? - Zuo, Youxia; Zhao, Yufang; Peng, Chunhua; Chen, Youguo (Frontiers in Psychology, 2017)
A tuition-free teacher candidate is an undergraduate who receives tuition-free teacher education and must work as a teacher in a middle school after their graduation. Tuition-free candidates are of the focus of many researchers; however, no study reports how tuition-free teacher candidates think about teachers. The present study explored stereotypes about middle school and university teachers held by teacher candidates. Specifically, we looked for the differences between the stereotypes held by the teacher candidates and general undergraduates. This study attempted to provide a potential tool to predict the actual willingness of teacher candidates to work as middle school teachers. University and middle school teachers were evaluated using descriptive phrases or words on a five-point Likert scale by 116 tuition-free teacher candidates and 155 general undergraduates. Exploratory factor analyses revealed a three-factor stereotype model including occupational cognition, occupational personality, and occupational emotion. Compared with general undergraduates, teacher candidates held more positive occupational personality and emotions toward middle school teachers; they held more negative occupational emotions toward university teachers. Further, the undergraduates’ willingness to be middle school teachers positively correlated with positive occupational emotions and negatively correlated with negative occupational personality and emotions toward middle school teachers. This supported previous studies that individuals’ professional willingness were influenced by their stereotypes about professions.